Study and Improvement of Manufacturing performance By Implementation of TPM - Prof. Ravi Ngaich, Pavan Kumar Malviya, (International Journal of Scientific Research and Management (IJSRM), 2015)
The purpose of this paper is to evaluate the contributions of total productive maintenance (TPM) initiatives towards improving manufacturing performance in Small and Medium scale Enterprises. In this paper we investigate the relationship between Total Productive Maintenance (TPM) and manufacturing performance (MP) and improving it by using the fundamental TPM Pillars and reducing the six big loses in a Manufacturing Industry